A facile biomass based approach towards hierarchically porous nitrogen-doped carbon aerogels. Issue 87 (5th September 2016) - Liu, Ruili; Xi, Xin; Xing, Xia; Wu, Dongqing
Abstract : Nitrogen-doped carbon aerogels with hierarchically porous architectures (NHCAs) are prepared via the hydrothermal treatment of cantaloupe and the following activation with potassium hydroxide. Abstract : Nitrogen-doped carbon aerogels with hierarchically porous architectures (NHCAs) are prepared via hydrothermal treatment of cantaloupes and the following activation with potassium hydroxide. The porous structure of the obtained NHCAs can be easily tuned by adjusting the activation temperature. Among the samples, the one activated at 800 °C (NHCA-800) exhibits the highest specific surface area of 1778 m 2 g −1 and the best electrochemical performance as both the electrode for a supercapacitor and the electrocatalyst for the oxygen reduction reaction, which is due to the co-existence of large amount of micro- and mesopores in NHCA-800.